The Complexities and Promise of Standing Beside Indigenous Literacy Scholars: A Language Curriculum Analysis - Brubacher, Katie; Filipek, Jacqueline (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Literacy is an essential component of any elementary-school classroom. To address shifting understandings of literacy and how to teach it, Alberta has developed a new language-arts curriculum. This curriculum, however, was developed in a context where schools have a long history of not serving Indigenous children well, including not meeting their needs through literacy programs (Hare, 2011). Alberta Education, through the English Language Arts and Literature (ELAL) curriculum, claims to better address those needs. The purpose of this research is to examine how the ELAL curriculum and its implementation aligns with the field of language and literacy, and in particular, Indigenous literacy scholarship, namely Peltier’s (2016/2017) Wholistic Anishinaabe Pedagogy and Reese’s (2018) Critical Indigenous Literacy. Data included both an analysis of the curriculum and semi-structured interviews with literacy instructors/scholars and in-service teachers. There were several key findings: English only processes, sparce attention to feelings throughout the curriculum, an absence of critical literacy, and inappropriate text selection. This paper is significant, as it shows the complexities and promise of being a non-Indigenous literacy scholar, thinking deeply about places of resonance and tension in literacy in ways that Indigenous scholars are already writing about.